Power distance in the implementation of a participatory action research project in a hierarchical society in Malaysia - Puteh-Behak F.; Saad N.S.M.; Ali U.M.; Darmi R.; Harun H.; Samah R. (American Scientific Publishers, 2024)
Indexed by SCOPUS/ERA